Reorienting the Filipino architect - Alarcon, Norma I. (2003)
Architectural education in the Philippines began towards the end of the Spanish era and continued to the American regime. These schools of architecture were established for the training of Master Builders or Maestro de Obras who were allowed to design wooden two-storey structures only. Faced with the enormous task of building up the Philippines, the American colonial government sent some Filipinos (scholars or pensionados) to undergo architectural training abroad. Upon their return to the country, the new architects brought with them foreign design concepts and styles that led to the emergence of an architecture that is quite unconventional to the Filipino culture. In the years that followed, architectural schools that conferred academic degrees were established. The earliest architectural curriculum was patterned from abroad. It has undergone several expansions and revisions in order to adapt to the needs of the times. Today, with about 45 schools of architecture in the country adopting a national curriculum, nowhere in the past and current programs can one find a specific study of western architecture and a semester in Asian architecture with only a few hours apportioned to Philippine study. Today's architectural curriculum explains the current state of architecture in our country and the kind of architectural thinking our professional architects have. There is an utter disregard for the preservation of our architectural legacies while countries abroad are doing massive restoration and conservation on theirs. This is regrettable considering that the Philippines is a culturally rich country. There is a need for the reorientation of the future Filipino architect and this must begin now. After all, architecture is the best cultural showcase of a nation.